2020
DOI: 10.1007/s00784-020-03197-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth and viability of Streptococcus mutans in sucrose with different concentrations of Stevia rebaudiana Bertoni

Abstract: Objective: To evaluate total absorbance, planktonic growth, biofilm formation, viability, metabolic activity and pH of Streptococcus mutans UA159 cultures when different dilutions of Stevia Rebaudiana Bertoni were applied and to determine the minimum inhibitory concentration (MIC) and the minimum biofilm inhibitory concentration (MBIC) of Stevia on S. mutans. Materials and methods: The effects of different dilutions of Stevia (0-400 mg/ml) on S. mutans total growth, planktonic growth, biofilm formation, viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 19 publications
2
20
1
1
Order By: Relevance
“…Además, reportan que la Stevia en diversas concentraciones aumenta el pH y disminuye la producción del ácido en el Streptococcus mutans (14) . Como también la reducción del recuento salival del Streptococcus mutans, y además aumenta el flujo lo cual evitara que se adhiera la bacteria y el aumento del pH salival para así lograr un efecto anticariogénico (5)(6)(7)15) . Por consiguiente, coincide con nuestra investigación que disminuye el factor de riesgo cariogénico del Streptococcus mutans (16) .…”
Section: Resultsunclassified
“…Además, reportan que la Stevia en diversas concentraciones aumenta el pH y disminuye la producción del ácido en el Streptococcus mutans (14) . Como también la reducción del recuento salival del Streptococcus mutans, y además aumenta el flujo lo cual evitara que se adhiera la bacteria y el aumento del pH salival para así lograr un efecto anticariogénico (5)(6)(7)15) . Por consiguiente, coincide con nuestra investigación que disminuye el factor de riesgo cariogénico del Streptococcus mutans (16) .…”
Section: Resultsunclassified
“…Escobar et al testi ied that S. mutans total growth and bio ilm formation showed a marked decrease with reduced concentrations of Stevia along with reduced bio ilm and acid production (Escobar et al, 2020). When it comes to microhardness, Maryam Kishta et al reported a loss of microhardness of bovine dentin with the use of 0.5% and 5% stevia extract (Kishta-Derani et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, assessments of disinfectants' efficacy have been largely based on growth inhibition of microbial cells. Growth‐dependent methods typically evaluate the sensitivity of cell growth to disinfectants through dilution and diffusion experiments and then derive quantitative parameters such as “minimum inhibitory concentration” (MIC) [ 14 ] to guide clinical drug usage. However, these methods are usually time and labor consuming (frequently over 24 h [ 15 ] ) and generally unable to tackle yet‐to‐be‐cultured microorganisms.…”
Section: Introductionmentioning
confidence: 99%